Peran Tokoh Agama dalam Mengatasi Perilaku Menyimpang di Desa Pipa Putih Kecamatan Pemulutan Kabupaten Ogan Ilir - Adelia Ananda; Hidayat HT; Anang Walian (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This undergraduate thesis is entitled “The Role of Religious Leaders in Addressing Deviant Behavior in Pipa Putih Village, Pemulutan District, Ogan Ilir Regency.” The purpose of this study is to identify the condition of deviant behavior and to examine the role of religious leaders in overcoming such behavior in Pipa Putih Village, Pemulutan District, Ogan Ilir Regency. This research employs a field research approach with a qualitative method. The data sources consist of primary and secondary data. Data collection techniques include observation, interviews, and documentation. Furthermore, the data were analyzed through several stages, namely data reduction, data display, and conclusion drawing. This study applies the theory of the role of religious leaders proposed by Imam Bawani and the theory of deviant behavior by Narwoko. The results of the study indicate that religious leaders play a significant role in addressing deviant behavior in the community through three main roles. First, the role of regeneration (cadre development), where Islamic religious leaders organize and carry out cadre-building activities within the community. Second, the role of service, where religious leaders actively engage with the community by providing guidance, assistance, and direction toward social improvement. Third, the role of da’wah (Islamic preaching), in which religious leaders strive to prevent inappropriate practices, guide individuals toward the right path, promote constructive ideas in various aspects of development, and raise awareness about achieving a better future life.